Particularistic and Universalistic Media Policies: Inequalities in the Media in Hungary - Bajomi-Lazar, Peter (Javnost-The Public, 2017)
In consolidated western democracies, contemporary approaches to media policy have largely been affected by the social responsibility theory of the press. A number of media policy measures have been designed and implemented in an attempt to counter market imperfections such as the concentration of media ownership and the resulting concentration of content as well as to compensate for the inequalities of access to the media created by the socio-economic disadvantages of some citizens. Such policy measures include, among other things, the establishment of public service media, the introduction of press subsidy systems and the allocation of frequencies to community radio stations. These can be described as universalistic media policy measures, and are aimed at equally distributing media resources. But what if a state intentionally pursues a particularistic media policy aimed at promoting some voices and discriminating other ones; that is, aimed at enhancing unequal access to media resources? The example of post-2010 Hungary shows the devastating effects of such a media policy regime.